Rebel cities by David Harvey: Revisiting marxist theory, the right to the city and urban struggle - Koç, Ersan (Bentham Science Publishers, 2023)
The book we will discuss is one of Harvey's most important works on the right to the city and Marxist theory and consists of 7 parts. This article aims to guide the readers via a summary of the content of the book. The introduction begins with the narrative that complex and stratified social classes have a greater impact on the transformation and revolution of cities than the working class employed in industrial spaces. In his book, Harvey repositions Marxist Political Theory as a basis for cities generating capital accumulation. This argument surpasses the general and misconceived belief that such effects are produced by factories and the labor force. The rationale for this argument is an economic one, depicting the importance of the capitalism of land, landrent, intellectual capital and speculation rather than commodity production. This commune is a very different kind of proletarian revolution, in which much of the leftist political chambers see an Avant-Guard spirit. In the preface part, Harvey draws attention to the increasing urbanization of the globe, which is frequently discussed under the effects of the post-colonial era. In the capitalist system, the urban process is fraught with extraordinary political turmoil, whose roots can be revealed in part through an examination of how urbanization is shaped by its interlocking concrete abstractions and is shaped directly by the circulation of money in space and time. The tensions between the individuality of the act of spending money and the class experience of earning that money divide the social and psychological foundations of political action. The book concludes with ideas portraying an unexpected unwillingness to put heavy importance on the political agency role of rioters, like the Wall Street Occupation. Harvey's theoretical artisan is highly valuable in putting the complex economic processes underlying urbanization and the inter-flows of capital in the form of urban space. Harvey comprehensively puts the notion of surplus capital, primarily through creative destruction-the large-scale restructuring of cities-in urbanization's central role. Rebel Cities is a needed book for a renewed case, a city as a medium for urban rights claimed and possessed by the public rather than forces of capitalism. © 2023 Bentham Science Publishers. All rights reserved.
Keywords: Accumulation; Authoritarianism; Autonomy; Capital; City; Class; Democracy; Discontent; Labour; Leftist; Liberalism; Marxism; Place; Policy; Public; Re-design; Rebel; Space; Struggle; Urban